Shuangwu paste in the treatment of chronic soft tissue injury caused by - Zeng, F.; Zhang, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Research indicates that in a sporting population, chronic soft tissue injury induced by physical exercise is prevalent. This study was an attempt to determine the preventive effect of Shuangwu paste on soft tissue injury, and to find an effective, safe and convenient therapy. Methods A total of 42 participants with chronic soft tissue injury induced by physical exercise were selected to participate. The treatment effects were determined through the use of a self-control study. Two kinds of treatments were used which included a reduction in exercise and application of Shuangwu paste on the injured areas and adjacent joints. The group was treated for six days. A period of two weeks between these two treatments was required. The standard evaluation of clinical effects of treatments was based on "The principles for clinical observation of "Traditional Chinese Medicines". Results Analysis of the results demonstrated that there was a significant difference between those treated by reducing exercise and the paste-treated group. The experimental group with paste therapy demonstrated significant efficiency of 57.7% and overall efficiency of 85.7%. Discussion / Conclusions The prescription of Shuangwu paste, an ancestral paste from a famous medical family in China, can be applied in the treatment of chronic soft tissue injury through a dressing using mixed Chinese medicine on the injured soft tissue area. The paste was created based on a long period of observation in clinical settings. The usage of this paste was recorded as an effective, convenient and safe treatment. The prescription included ligusticum, frankincense, myrrh, dragon`s blood, chaenomeles, duhuo, aconite main tuber, wild aconite and musk. It is suggested that the ligusticum can quicken qi and blood so as to release pain, whereas frankincense and myrrh can quicken the blood and dispel stasis. The dragon`s blood can release the feeling of pain. These three are key traditional medicines to treat pain caused by stasis. Musk can dissipate stasis to regulate our meridians and collaterals. The study indicated that Shuangwu paste may be applied as an effective, safe and convenient treatment in the management of chronic soft tissue injury caused by physical exercise.